2007
DOI: 10.1152/ajpcell.00204.2006
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor-dependent increases in nitric oxide synthase expression in the pulmonary endothelium is mediated via a Gαi3/Ras/Raf/MAPK pathway

Abstract: SC. Angiotensin II type 2 receptor-dependent increases in nitric oxide synthase expression in the pulmonary endothelium is mediated via a G␣i3/Ras/Raf/MAPK pathway. Am J Physiol Cell Physiol 292: C2185-C2196, 2007. First published February 28, 2007 doi:10.1152/ajpcell.00204.2006.-We have previously reported that angiotensin II (ANG II) stimulated Src tyrosine kinase via a pertussis toxin-sensitive type 2 receptor, which, in turn, activates MAPK, resulting in an increase in nitric oxide synthase (NOS) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Evidence of ICL3 involvement was also shown in AT 2 receptor induction of apoptotic responses in the PC12W neuronal lineage cells and in AT 2 receptor-mediated inhibition of IP 3 generation in Xenopus oocytes (Kumar et al, 2002). More recent studies implicated the involvement of G i in AT 2 receptor-dependent increases in nitric oxide synthase expression (Li et al, 2007a) and the inhibition of proximal tubule Na + -ATPase by Ang(1-7) Gohlke et al, 1998;Siragy, 2000). The production of prostacyclin in differentiated adipocytes was blocked by PD123177 and not by losartan, which suggests that this is an AT 2 receptor-mediated signal (Darimont et al, 1994).…”
Section: E Signalingmentioning
confidence: 84%
“…Evidence of ICL3 involvement was also shown in AT 2 receptor induction of apoptotic responses in the PC12W neuronal lineage cells and in AT 2 receptor-mediated inhibition of IP 3 generation in Xenopus oocytes (Kumar et al, 2002). More recent studies implicated the involvement of G i in AT 2 receptor-dependent increases in nitric oxide synthase expression (Li et al, 2007a) and the inhibition of proximal tubule Na + -ATPase by Ang(1-7) Gohlke et al, 1998;Siragy, 2000). The production of prostacyclin in differentiated adipocytes was blocked by PD123177 and not by losartan, which suggests that this is an AT 2 receptor-mediated signal (Darimont et al, 1994).…”
Section: E Signalingmentioning
confidence: 84%
“…Furthermore, it appears that up-regulated eNOS expression and subsequently enhanced NO production are mediated via AT2R activation, involving G alpha i3/Ras/Raf/MAPK (ERK) pathway[17,18]. Therefore, we hypothesized that AT2R/p-ERK/eNOS/NO pathway activation would be account for the cardioprotective effects conferred by preconditioned BMMNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Such effects can be abolished when AT2R antagonist was added, suggesting that AT2R signaling could also promote the paracrine action of BMMNCs which support the survival of NRCMs. Several studies has clearly shown that AT2R stimulation can induce pulmonary artery relaxation through enhanced eNOS expression and NO releasing[17,18]. Pretreatment with eNOS enhancer AVE9488 increases NO generation of bone marrow mononuclear cells and improves their functional activity in a murine model of unilateral hind limb ischemia[29].…”
Section: Discussionmentioning
confidence: 99%
“…AT1R signaling occurs principally via Ga q11 and involves the production of inositol trisphosphate and mobilization of intracellular Ca 2+ ; in contrast, AT2Rs commonly signal through Gai3 to activate the NO/ cGMP pathway . 30,31 In nuclei isolated from atrial fibroblasts, AT2Rs were responsible for Ang-II-dependent NO production, since the AT1R-selective antagonist valsartan had no effect on DAF-2 fluorescence, whereas the AT2R-selective antagonist PD 123,319 reduced DAF-2 fluorescence to levels similar to those observed when nuclei were pretreated with NOS inhibitor, L-NAME. Consistent with previous findings in fibroblast nuclei isolated from whole heart, endothelial NOS immunoreactivity was detected in nuclei isolated from fibroblasts.…”
Section: Nuclear Atr-effector Coupling In Fibroblastsmentioning
confidence: 93%